The abundances and distribution of some trace elements in some selected South African shales - Hofmeyr, Pierre Karel (Department of Environmental and Geographical Science, 2024)
This thesis is the study of a single farm, Klaver Valley in the Darling district, 1812 - 1898. Chapter One provides a physical view of Klaver Valley from 1812 to 1898 showing the changes in the landscape and production of grains, wine and wool over the period. It argues that these changes occurred as a direct result of external market forces. Chapter Two focuses on the changes which occurred in the labour process from the early 1800s to 1898, arguing that the main impetus for change came from mechanisation of harvesting in the 1820s and 1850s. Chapter Three explores the notion of a capitalist farmer and argues that Duckitt and later Ruperti can be categorised as capitalist farmers. The main thrust of their progressive capitalization occurred before the 1850s and it did so as a result of the system of informal credit which existed at farm level among farmers, allowing for re-investment and survival of cash flow. Chapter Four studies the process of proletarianisation which accompanied the capitalist development of the farm and its farmers. While taking account of the existence of a small number (3) of sharecroppers on the farm in the 1840s, 1870s and 1890s, this chapter argues that by the early 1830s, the farm was operating on the back of fully proletarianised labour. Composition of the labour force, wages and tasks, the work of women and the change from resident and permanent to casual labour from the 1820s to the 1890s, form some of the main focuses of this chapter. Chapter Five explores the nature of the relationship between the farmer and workers from - 1898, the two increasingly alienated from each other by the encroachment of the overseer. It argues that capitalist relations of production developed in the context of paternalism throughout although it was increasingly shaped by the cash-oriented relationship.